2014
DOI: 10.1159/000360646
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Supplementation in the Neonatal Period: Changing the Paradigm

Abstract: Oxygen is one of the most widely used drugs in the neonatal period. A lack of knowledge of oxygen metabolism and toxicity has prompted guidelines to fluctuate from liberal use to treat respiratory distress to restriction to avoid retinopathy of prematurity. In recent years, studies performed in the immediate postnatal period have revealed that newly born infants achieve a stable saturation only several minutes after birth. Moreover, the time needed to reach a saturation plateau is inversely proportional to a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
43
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 54 publications
0
43
0
1
Order By: Relevance
“…A recent randomized controlled trial demonstrated that, after postnatal stabilization, keeping preterm babies within a high saturation target range (91-95%) increases the risk of ROP as compared to keeping them in a lower saturation range (85-89%) [9]. However, the lower saturation target resulted in a significantly higher risk of mortality compared to the higher saturation range; hence, the present protocol of oxygen supplementation recommends keeping the oxygen saturation within stringent security margins (90-95%) [10,11]. Although the impact of different oxygen supplementation conditions on the development of severe ROP has not been fully clarified, a recent report described that the significant risk factors for Indian ROP included a longer duration of ventilation and higher inspiratory oxygen (FiO 2 ) [12].…”
Section: Introductionmentioning
confidence: 99%
“…A recent randomized controlled trial demonstrated that, after postnatal stabilization, keeping preterm babies within a high saturation target range (91-95%) increases the risk of ROP as compared to keeping them in a lower saturation range (85-89%) [9]. However, the lower saturation target resulted in a significantly higher risk of mortality compared to the higher saturation range; hence, the present protocol of oxygen supplementation recommends keeping the oxygen saturation within stringent security margins (90-95%) [10,11]. Although the impact of different oxygen supplementation conditions on the development of severe ROP has not been fully clarified, a recent report described that the significant risk factors for Indian ROP included a longer duration of ventilation and higher inspiratory oxygen (FiO 2 ) [12].…”
Section: Introductionmentioning
confidence: 99%
“…In order to avoid hyperoxia, current recommendations advise resuscitation of preterm infants with a mixture of air and oxygen, and to use fraction of inspired oxygen (FiO 2 ) between 0.21 and 0.30 (9). FiO 2 should subsequently be titrated according to SpO 2 (10,11). General use of pulse oximetry has been shown to extensively reduce O 2 -derived toxicity in preterm infants (12).…”
mentioning
confidence: 99%
“…In a paper from 2014, Vento (36) showed, in 5000 newborns with very low birth weight and gestation <28 GW, that premature babies who have SaO 2 in the region of 91-95% up to 36 GW, have significantly lower mortality and fewer severe disabilities than newborns with low SaO 2 (85-89%). It is still not known whether SaO 2 should be constant during this post-natal period, or if it should be reduced or even increased during infections, stagnation in growth, ROP and BPD.…”
Section: Discussionmentioning
confidence: 99%